Local Elites as Collaborative Networks: A Systematic Literature Review Analysis of Their Capabilities and Roles in Regional Development - Tarom, Muhamad; Aksuo, Muhammed (Universitas Pancasakti Tegal, 2025)
Local elites play a central role in regional development, yet the existing literature is fragmented on the economic and political aspects of electoral politics without providing a comprehensive explanation of their capabilities in creating high-performance governance and holistic development achievements. This study aims to analyse the multidimensional role of local elites in building collaboration and mobilising community participation to achieve quality governance. Using a systematic literature review method guided by PRISMA, this study analysed 10 selected articles from the Scopus database identified through the keywords